2013
DOI: 10.1186/1748-717x-8-47
|View full text |Cite
|
Sign up to set email alerts
|

Risk of second cancer from scattered radiation of intensity-modulated radiotherapies with lung cancer

Abstract: PurposeTo compare the risk of secondary cancer from scattered and leakage doses following intensity-modulated radiotherapy (IMRT), volumetric arc therapy (VMAT) and tomotherapy (TOMO) in patients with lung cancer.MethodsIMRT, VMAT and TOMO were planned for five lung cancer patients. Organ equivalent doses (OEDs) are estimated from the measured corresponding secondary doses during irradiation at various points 20 to 80 cm from the iso-center by using radio-photoluminescence glass dosimeter (RPLGD).ResultsThe se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
1
15
1
Order By: Relevance
“…Thus, low doses to the whole body were increased, and secondary malignancy risk was increased even though this is controversial. 6,30,31 Our studies showed the same results as literature data for IMRT and VMAT comparison. OAR sparing was the same for both techniques.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, low doses to the whole body were increased, and secondary malignancy risk was increased even though this is controversial. 6,30,31 Our studies showed the same results as literature data for IMRT and VMAT comparison. OAR sparing was the same for both techniques.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies suggest that increase in MU results in increased SCR, and these studies attributed it to increased head leakage and collimator scatter. [ 31 32 ]…”
Section: Discussionmentioning
confidence: 99%
“…Second cancer risks for in-field organs were more than for organs outside of treatment field with an exception for ITF and VMAT plan [16]. Optimization and conformation to treated volume consequence reduce in relative OED in all three relationships dose-response.…”
Section: Organ Equivalent Dosementioning
confidence: 99%
“…Where TOMO, is less than or compatible with the secondary of the dose and OED from conventional IMRT and VMAT but TOMO is similar to IMRT and VMAT as increasing the distance from the field edge [16]. Organs near to the PTV have rising risk to stimulate second cancer [25].…”
Section: Organ Equivalent Dosementioning
confidence: 99%